Proposal of a Cooling Device with Peltier Cells Powered by an Independent Photovoltaic System: A Case Study (2021)
Currently, multiple studies are trying to establish alternatives that will allow for the reduction of the consequences of energy consumption and greenhouse gases. In this sense, photovoltaic solar energy has become a feasible option to alleviate this problem, also, new technologies have been sought to reduce the energy consumption of cooling devices, because they consume too much energy and use harmful refrigerants to accomplish their task. For this reason, Peltier cells can be a viable option to lower the temperature in closed spaces without generating waste or harmful emissions. In the present work, we propose to combine these initiatives in a unified system to take advantage of both technologies, implementing a cooling system that uses the thermoelectric effect to reduce the temperature inside, which is fed by an autonomous photovoltaic system using maximum power point tracking algorithms to improve its performance. The results show that the device is capable of lowering the temperature inside, allowing the conservation of elements at low and constant temperatures, without the disadvantages of common refrigerators. Finally, it is concluded that this system is a plausible possibility to replace cooling technologies where access to electrical energy is limited.